Smallanthus sonchifolius (Yacon) Flour Improves Visceral Adiposity and Metabolic Parameters in High-Fat-Diet-Fed Rats - Stella Maris Honoré; Maria Virginia Grande; Jorge Gomez Rojas; Sara Serafina Sánchez (Hindawi Limited, 2018)
Smallanthus sonchifolius (yacon), a native plant of South America, was observed to improve lipid profile in rodents and humans. This study aimed to investigate the antiobesity properties of yacon roots in a high-fat-diet (HFD) model and the underlying mechanisms. A total of 30 Wistar male rats were divided into five groups (n=6): the standard chow diet (SD) group was fed a SD; the HFD group was fed a HFD; and the HFD Y340 and HFD Y680 groups were fed a HFD plus yacon flour (340 and 680 mg FOS/kg b. w./day, respectively). HFD Y340 and HFD Y680 rats exhibited marked attenuation of weight gain, a decrease in visceral fat pad weight, a restoration of the serum lipid profile and atherogenic index in a dose-dependent manner, being the higher dose more effective (p<0.05). In addition, we found that HFD Y680 rats showed lower glucose and insulin levels, improved glucose tolerance, and insulin sensitivity (p<0.5). A downregulation of several adipocyte specific-transcription factors, including peroxisome proliferator-activated receptor gamma2 (PPAR-γ2), CCAAT/enhancer binding protein a (C/EBP-a) and activating protein (aP2) mRNA levels, was determined in the visceral adipose tissue of HFD Y680 rats (p<0.05). An improvement of adipokine profile in HFD Y680 rats and decreased serum proinflammatory cytokine levels (p<0.05) were determined by ELISA. Decreased macrophage infiltration and F4/80 and MCP-1 expression in the visceral adipose tissue of HFD Y680 rats (p<0.5), together with a higher pAkt/Akt expression (p<0.05) were also observed by immunofluorescence and immunoblotting. A significant increase in glucagon (Gcg) and PYY mRNA levels in distal ileum of HFD Y680 rats (p<0.05) were also detected. In the second approach, we determined that yacon supplementation potentiates the effects of the HFD reversion to a standard diet. In conclusion, yacon showed antiobesity properties by inhibiting adipogenesis and improving the visceral adipose tissue function.